The New Horizons of Law and Science through the lens of the Agenda 2030 on Sustainable Development. Some Emerging Issues - Poto, Margherita Paola; Murray, Emily (Environmental Policy and Law, 2022)
The complex sustainability challenges of the 21st century need to be addressed through integrated interdisciplinary approaches, combining science, law, and ethics with concrete, timely, and effective solutions. This study offers a legal framework and a case study to the needs posited by the Agenda 2030 on sustainable development. Starting from an analysis of the first part of the Agenda, the article unfolds by exploring the possibility of defining environmental compliance through environmental responsibility, environmental duties, and the virtuous case of agroecology. The case study focuses on a climate-smart practice applied to the sea and delves into the environmental, nutritional, and health benefits of the marine biomass from Northern Norway. The theoretical framework and the case study will emphasize the importance of systemic approaches to sustainability for putting integral ecology models into action.